Growth and Yield The First Generation (M1V1) of Local Shallot Humbang Hasundutan Genotypes Accession of Tipang Irradiated by Gamma Ray mentored - Bobby Frans Natanael; ferry ezra sitepu; Mariati sinuraya (Jurnal Agroekoteknologi, 2018)
The aim of the research was to determine the growth and yield the first generation (M1V1) of local shallot Humbang Hasundutan genotypes accession of Tipang irradiated by gamma ray. Research was conducted at Rianiate village, Pangururan Samosir district at altitude ± 1010 meters above sea level began from July up to October 2016. The experiment was arranged by augmented design with six level dosages of gamma irradiation i.e; 0; 2; 4; 6; 8; and 10 Gy. The data was analyzed with T test using Minitab 16 software. The Parameters observed were plant lenght, number of leaves, number of tillers, fresh and dry weight of tubers, and tuber diameter. The result showed, that the genotypes shallot that were irradiated with gamma rays at 8 Gy produced better growth and yield than control plants (unirradiated plants).